1976
DOI: 10.1071/ar9760489
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and storage limitations to yield in Sorghum bicolor (L. Moench)

Abstract: Under favourable growing conditions, the source-sink relationships in grain yield of sorghum were analysed in terms of capacities for net assimilation, of head storage, and of the transport system to move assimilates between source and sink. In four commercial hybrids (Dekalb E57, Pacific Goldfinger, Texas 610SR, and Texas 626) grown at three population densities (20.2, 40.4 and 80.8 plants m-1), the assimilates supply was varied by increasing or decreasing the radiation available per plant (by thinning or sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Studies where removal of sink components led to compensatory growth in remaining components supported the hypothesis that the source rather than the sink was limiting (Muchow and Wilson 1976;Yong-Zhan et al 1996). Compensatory growth of this nature was demonstrated in sugarcane by removal of 25, 50, or 75% of the plants in field plots, 4 months before harvesting, at which time biomass yields were reduced by only 4, 30, and 63%, respectively, because of increased dry mass of the remaining plants (Bell and Garside 2005).…”
Section: Discussionmentioning
confidence: 78%
“…Studies where removal of sink components led to compensatory growth in remaining components supported the hypothesis that the source rather than the sink was limiting (Muchow and Wilson 1976;Yong-Zhan et al 1996). Compensatory growth of this nature was demonstrated in sugarcane by removal of 25, 50, or 75% of the plants in field plots, 4 months before harvesting, at which time biomass yields were reduced by only 4, 30, and 63%, respectively, because of increased dry mass of the remaining plants (Bell and Garside 2005).…”
Section: Discussionmentioning
confidence: 78%
“…However, this previous assumption is inconsistent with the observations that seed growth is arrested when the soil becomes very dry (Muchow 1989) and that decreased grain mass and final harvest index in cereals under post-anthesis drought stress is a consequence of a shorter grain filling duration, rather than a decreased grain growth rate (Bieler et al 1993;Frederick and Camberato 1995;Li et al 2000). Nevertheless, the capacity of sorghum to transfer stored reserves to the seeds (Muchow and Wilson 1976) assures that the final harvest index will achieve at least a minimum value. Hence, in a manner similar to that used in the sorghum model of Hammer and Muchow (1994), the linear increase in harvest index was maintained at the same daily rate, but the increase was stopped whenever the soil dried to a fraction of transpirable soil water equal to or less than 0.1 and a minimum harvest index of 0.2 had been reached (Kamoshita et al 1998).…”
Section: Model Descriptionmentioning
confidence: 73%
“…Obviously the plants were able to compensate the sudden loss of sink capacity completely by subsequently producing new flowers and seeds. Muchow and Wilson (1976) suggested that sorghum spikelets that would abort under normal conditions remain viable when competition is reduced by spikelet removal. This could also apply in the present case of amaranth but was not studied.…”
Section: Resultsmentioning
confidence: 99%
“…In soybean (Liu et al 2006, Proulx andNaeve 2009), sunflower (Charlet and Miller 1993), and sorghum (Muchow and Wilson 1976), removal of flowers, pods or spikes resulted in increased grain size but yield reduction. Also in wheat and maize, individual grain mass could partly compensate for reduced grain numbers , Oveysi 2010) but did not always respond (Borras et al 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation